As vestimentas do mártir : as representações sobre Tiradentes em Joaquim Norberto de Souza Silva e Lúcio José dos Santos e a narrativa da nação no discurso didático - Gama, Luciana Coelho (2016)
This present study aims to analyze discursive representations produced bymonarchistand republicanintellectuals about Tiradentes, it’s having as sources the historiographicaland didacticworks of the Nineteenth Century and early Twentieth Century. We have examined the content of the sources in question by checking thediscourses about the lieutenant and his role in the InconfidênciaMineira, where monarchist intellectuals tend to portray him as mediocre character and mere inconsequential loudmouth, while Republicans see it as founder and leader of Minas Gerais’s movement. We used as theoretical basis Jean-François Sirinelli precepts, understanding intellectuals as creators of culture; Michel de Certeau, regarding the influence of the author placeof speaks in historiographical discourse; the Roger Chartier’sconcepts of appropriation and representation to understand the different versions of the facts created by historians from the same evidence base, and the premises of Stuart Hall to think about the construction of national identity through history textbooks. The objective is to demonstrate how the historical ―true‖ is built under the influence of time contexts in which they live their producers — intellectual historians — it’s being spread in the literate means and educational institutions.